FAKTOR-FAKTOR YANG MEMPENGARUHI ALOKASI BELANJA KESEHATAN PADA KABUPATEN/KOTA DI PROVINSI ACEH - Darmayanti, Cici; Unisyiah, Nadirsyah; Abdullah, Syukriy (JURNAL KEBANGSAAN, 2016)
The objective of this study is to test the effect of special autonomy fund allocation, special allocation fund, infrastructure expenditure allocation, population, health ranking, and local government financial performance to health expenditure allocation in districts/cities in Aceh. The population in this study was 23 districts/cities in Aceh with observation period from 2011 to 2012. The approach and method used are quantitative and multiple linear regression. The study results show that, both simultaneously and partially, the variables of special autonomy fund allocation, special allocation fund, infrastructural expenditure allocation, population, health ranking, and local government financial performance have significant effect on health expenditure allocation in districts/cities in Aceh. In next study, the researcher recommends to use time series data and to add more independent variables. Keywords: special autonomy fund, special allocation fund, health ranking, local government financial performance and health expenditure.